Aqua sense / Muhammad Haziq Razak - Razak, Muhammad Haziq (2024)
The concept of the smart aquarium has received significant attention in recent years, which is it offers a modern technology for the people that loves to keep fish as their hobbies. With the modern technology and tools, it provide a range of automated functions, real time monitoring and give more experience to the user. The benefits for this system are the condition of the aquarium and the fish can be managed by only using the system automatically. For example, the user no need to use the thermometer to identify the temperature of the water, no need to monitor the water level of the water level manually, and the quality of the water will be monitor by the system. With this system, the user can save their time to do their work without always worrying about the condition of their aquarium and fish